PENGARUH KINERJA KEUANGAN TERHADAP REAKSI PASAR PADA PERUSAHAAN MANUFAKTUR - Yulindasari, Eka Pungky; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The purpose of this research is to examine the influence of current ratio, debt to equity ratio, return on asset,total asset turnover to the market reaction. The population is all consumer goods industry sector manufacturingcompanies which are listed in Indonesia Stock Exchange in 2012-2014 periods. The sample collection techniquehas been done by using purposive sampling with predetermined criteria so 17 sample companies with 3 yearobservations. The data analysis has been carried out by using multiple linear regressions analysis. The result ofthe research shows that 1) current ratio, 2) total asset turnover give positive influence to the market reactionwhereas 3) debt to equity ratio give negative influence to the market reaction. Meanwhile, 4) return on asset doesnot give any influence to the market reaction. It has been found from the formulation of four hypothesis, threehypothesis are suported by the result of the research whereas one hypothesis i.e. the influence of return on asset tothe market reaction is not supported by the result.Keywords: Current ratio, debt to equity ratio, return on asset, total asset turnover, market reaction.